An alien in Marseille: investigations on a single Aedes aegypti mosquito likely introduced by a merchant ship from tropical Africa to Europe - Jeannin Charles; Perrin Yvon; Cornelie Sylvie; Gloria-Soria Andrea; Gauchet Jean-Daniel; Robert Vincent (Parasite, 2022)
Control of invasive species relies partly on permanent surveillance at international points of entry. We report the exceptional trapping of one adult mosquito (Diptera: Culicidae) in the port of Marseille, France, in July 2018, during a routine survey conducted according to International Health Regulations. Morphological and molecular identification classified the specimen as a female Aedes (Stegomyia) aegypti (L.), vector of many arboviruses, absent from Europe and the Mediterranean rim since the 1950s. A world reference panel of approximately 23,000 genome-wide single nucleotide polymorphisms determined that the mosquito originated from Cameroon, west Africa. Cross-reference of this geographic location with boats traveling from Central Africa to Marseille during the trapping period suggests that the mosquito travelled within an identified merchant ship, a vehicles carrier connecting Douala, Cameroon to Marseille, France. This ship left Douala on June 25, 2018 and arrived 20 days later in Marseille on July 15. The mosquito was captured 350 m away from the dock. The interception of a propagule of an invasive species is a rare event that must be considered a priority to prevent its successful establishment.